Pembelajaran Bahasa Indonesia / Teknik Penulisan Karya Ilmiah di Institut Agama Islam Qamarul Huda Bagu Lombok Tengah - Syarifudin Syarifudin (Sekolah Tinggi Agama Islam al-Amin, Gersik, Kediri, Lombok Barat, NTB, 2019)
The TPKI/Indonesian language learning is divided into two, namely (1) language which consists of providing words, sentences, discourses, and scientific writing techniques. This is adjusted to the research methodology and adapted to the guidelines for writing a thesis at the Qamarulhuda Islamic Institute. Regarding language learning, it is taught by practicing directly using newspaper media. The method used in linguistic practice, students are given the task of finding a title in the newspaper and then are required to state paragraphs, paragraph names and find writing errors. (2) Learning TPKI (Scientific Writing Techniques) is carried out in groups. Students are divided into three groups. The group consists of qualitative, quantitative and literature review groups. The material that must be reported is finding the problem, compiling the basic title of the problem finding, identifying the problem, how to solve the problem, discussing the problem and making conclusions. Whereas, in writing the report, it must pay attention to the Indonesian language writing guidelines.